Credit Transfer, Articulation & The Future of Work: Towards a Federal Strategy - Pizarro Milian, Roger; Munro, Yvette (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
Some analysts foresee that the rise of automation—triggered by advances in artificial intelligence, robotics, and other novel technologies—will soon unsettle sizable sections of our labour market, prompting the need for mass upskilling and re-skilling. Continuous learning is perceived as the new norm within the future of work. Many believe that solutions to future surges in training demand will require a degree of dexterity not exhibited by traditional postsecondary education (PSE) organizations, and advocate for radical alternatives. However, we outline how basic reforms leading to a more robust articulation and credit transfer system could also improve our PSE system’s ability to handle augmented training demands. In turn, we explore how the Canadian federal government can facilitate these reforms by (a) providing additional incentives for domestic colleges and universities to engage in seamless transfer, and (b) supporting the production of knowledge to inform more strategic forms of pathway articulation.